Population structure in Quercus suber L. revealed by nuclear microsatellite markers - Filipe Sousa; Joana Costa; Carla Ribeiro; Marta Varandas; Francisco Pina-Martins; Fernanda Simões; José Matos; Maria Glushkova; Célia Miguel; Maria Manuela Veloso; Margarida Oliveira; Cândido Pinto Ricardo; et al. (PeerJ, 2022)
Quercus suber L. is a sclerophyllous tree species native to the western Mediterranean, a region that is considered highly vulnerable to increased temperatures and severe dry conditions due to environmental changes. Understanding the population structure and demographics of Q. suber is essential in order to anticipate whether populations at greater risk and the species as a whole have the genetic background and reproductive dynamics to enable rapid adaptation. The genetic diversity of Q. suber has been subject to different studies using both chloroplast and nuclear data, but population structure patterns remain unclear. Here, we perform genetic analyses on Q. suber using 13 nuclear microsatellite markers, and analysed 17 distinct locations across the entire range of the species. Structure analyses revealed that Q. suber may contain three major genetic clusters that likely result from isolation in refugia combined with posterior admixture and putative introgression from other Quercus species. Our results show a more complex structure scenario than previously inferred for Q. suber using nuclear markers and suggest that different southern populations contain high levels of genetic variation that may contribute to the resilience of Q. suber in a context of environmental change and adaptive pressure.